2018
DOI: 10.4236/ojl.2018.71005
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Leadership Theories

Abstract: Leadership is governed by over 66 theories which leaves many leaders and leadership scholars searching for an inclusive leadership theory. The existence of too many leadership theories obstructs progressive practice and research of leadership, hence there is need for leadership theory consolidation. This paper is an attempt to integrate leadership theories. The integration efforts are based on representative leadership theories and the review of the wider relevant leadership literature. Initially, the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 65 publications
(87 reference statements)
1
34
0
5
Order By: Relevance
“…In Higher Education Institutions, leadership and leadership style play an important role in order to have a robust institution. It is reasonable that the leadership style followed by the Head of the educational institution does not create the feeling of oppression and the imposition of force on the lower-level academics and on the administrative and other staff of the Foundation [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Higher Education Institutions, leadership and leadership style play an important role in order to have a robust institution. It is reasonable that the leadership style followed by the Head of the educational institution does not create the feeling of oppression and the imposition of force on the lower-level academics and on the administrative and other staff of the Foundation [4,5].…”
mentioning
confidence: 99%
“…The same research presented evidence that reinforces the view that leadership is a multilevel concept and that it can influence parameters that affect educational organizations and students. The Pandemic with COVID19 that still affects global communities highlighted even more urgently the need that educational leaders and the academic community at all levels ought to possess digital skills [5]. Today more than ever the importance of the digital leader has emerged, since without them the process of the digital transition that was applied in the universities of Greece could not be implemented in order to complete smoothly the educational process.…”
mentioning
confidence: 99%
“…This notion of coherence in both the PABC systems and in leader character development is an important shift. Currently, leadership theories and leader development are often compartmentalized (Mango, 2018), and this compartmentalization tends to neglect the important connective tissue that creates coherence, thus running the risk of turning potential virtues into vices by emphasizing one facet of the overall system and losing sight of others (Crossan et al, 2017). Focusing on coherence may help to address current conundrums in leadership, such as the "too much of a good thing" phenomenon (Antonakis et al, 2017), where the relationship between intelligence quotient (IQ) and perceived leader effectiveness is found to be curvilinear in an inverted U, indicating a moderate IQ at about the 120 range is better than lower and higher.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…According to Mango (2018), leadership theories can be stated into two types which are process theories and trait theories. The earliest study of theory, trait theory, is the first attempt on the study of leadership, which is about great man theory.…”
Section: Project Successmentioning
confidence: 99%
“…Ayman & Lauritsen (2018) showed that several organizational contingencies and multi-personal with interpersonal behaviors had influenced the concept of leadership. Mango (2018) mentioned that the leadership style has an impact on organizational performance or its effectiveness. The leadership style is fundamental in the organization's culture on how the job has been done and how people's relationship to perform the job is the aspect of human behavior.…”
Section: Emotional Intelligencementioning
confidence: 99%